Analyzing the adverse events of NK-1 receptor antagonists: a pharmacovigilance study from the FAERS database - Hong Pan; Xiang Shi; Yiguo Jiang; Jiaqiang Wu; Li Shen (Scientific Reports)
Abstract Background NK-1 receptor antagonists (NK-1RAs) are proven to be successful in preventing chemotherapy-induced nausea and vomiting (CINV). The safety profile of NK-1RAs has not been systematically analyzed in the real world. This pharmacovigilance study investigated the differences in adverse events (AEs) between NK-1RAs. Methods Adverse events (AEs) associated with NK-1RAs were gathered and standardized using data from the FAERS database spanning from the first quarter of 2009 to the fourth quarter of 2023. Various disproportionality techniques were employed for data analysis, such as the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS). Results A total of 5434AE reports listing NK-1RAs as the primary suspected drugs were identified. The System Organ Classes (SOC) appeared as significant safety signals were found. Among NK-1RAs, the most frequently reported AEs were related to general disorders and administration site conditions. In terms of PT level, the strong signals were mainly injection site reactions associated with aprepitant and fosaprepitant. Moreover, toxic encephalopathy and encephalopathy of the aprepitant were all positive with four algorithms. A significant finding was the recognition of adverse events linked to endocrine disorders, which were not previously mentioned in the medication instructions. Conclusion The safety profile of NK-1RAs has been reported to be variable.If intravenous formulations were used in the clinic, injection site reactions should be a concern. In addition, more attention should be paid to the management of encephalopathy toxicity in patients treated with aprepitant in combination with ifosfamide. Besides known AEs, we have identified several new high-risk AEs, such as inappropriate antidiuretic hormone secretion, adrenal insufficiency and hyponatraemia. Overall, clinicians should closely monitor the occurrence of NK-1RA-related AEs in clinical applications.